High-frequency Driving Circuit and Loss Analysis of SIC MOSFET Based on Discrete Components - Yue, Gai-Li; Wang, Zi-Jing; Xiang, Fu-Wei; Xu, Zhen-Zhen (Journal of electrical engineering & technology, 2024)
To reduce the loss of the high-frequency drive circuit of silicon carbide metal oxide semiconductor transistor (SiC MOSFET) and to better utilize the performance of the SiC MOSFET, a high-frequency drive circuit based on discrete components (DC-RGD) is proposed in this paper. The inductance is added to provide a low-impedance circuit for the gate charge/discharge circuit of the SiC MOSFET, enhancing the circuit’s immunity to interference. At the same time, an auxiliary switching tube is added to form an active clamping circuit to reduce the impact of parasitic parameters on the drive waveform in high-frequency applications. A negative voltage is generated by adding a series capacitor to the drive circuit, ensuring the auxiliary switch is on during SiC MOSFET turn-off. This switch is not driven by an additional drive circuit, thus simplifying the circuit. The operation and losses of the circuit are analyzed, and the design methodology of the circuit is given. Finally, a Boost converter with an input of 24 V and an output of 48 V/5 A is constructed. The operating waveforms at a frequency of 0.5 MHz are tested, and the loss of the driving circuit is only 0.317 W. The results show that the proposed driving circuit ensures the reliability of the SiC MOSFETs and is able to solve the problem of the driving waveform oscillations efficiently, with a better anti-interference capability and lower loss.